2019
DOI: 10.1155/2019/1401402
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Climate Change on the Growth of Typical Crops in Karst Areas: A Case Study of Guizhou Province

Abstract: Climate change has emerged as a significant man-made global environmental challenge marked by rising temperature. The global rising temperature is supposed to alter climatic patterns like floods and droughts, thereby affecting human life supporting system and global food production. In order to clarify the impact of weather events on agricultural production in karst landforms, this study selected the indices of the growth period of crops (start time and duration), growing season precipitation, intense precipit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 27 publications
2
4
0
Order By: Relevance
“…The main findings of the two-way fixed effects (2FE) regression and the multiple regressions for each province confirmed the expectation that the effects of climate change (increased temperature and decreased precipitation) have an impact on food production (maize and wheat yields). The results of this study are in line with the theory of increasing mean temperatures, as confirmed by Ma et al (2019). The rising global mean temperature is thought to change climatic patterns such as floods, droughts, and incidents of the El-Niño and La-Niña, thus affecting human life and global food production and having a negative effect on the main pillars of food security: availability, accessibility, utilisation and system stability (Ma et al, 2019).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The main findings of the two-way fixed effects (2FE) regression and the multiple regressions for each province confirmed the expectation that the effects of climate change (increased temperature and decreased precipitation) have an impact on food production (maize and wheat yields). The results of this study are in line with the theory of increasing mean temperatures, as confirmed by Ma et al (2019). The rising global mean temperature is thought to change climatic patterns such as floods, droughts, and incidents of the El-Niño and La-Niña, thus affecting human life and global food production and having a negative effect on the main pillars of food security: availability, accessibility, utilisation and system stability (Ma et al, 2019).…”
Section: Discussionsupporting
confidence: 86%
“…The results of this study are in line with the theory of increasing mean temperatures, as confirmed by Ma et al (2019). The rising global mean temperature is thought to change climatic patterns such as floods, droughts, and incidents of the El-Niño and La-Niña, thus affecting human life and global food production and having a negative effect on the main pillars of food security: availability, accessibility, utilisation and system stability (Ma et al, 2019). Further to this, studies show that the worldwide mean temperature has risen by 0.74°C during the past 100 years (Misra, 2014).…”
Section: Discussionsupporting
confidence: 86%
“…Although the forest in CRR suffers more drought stress, the vegetation activity only exhibits slightly lower values than those in NCRR (Figure 3). One possible reason for that is that the trees in the karst environment develop several special adaptabilities against drought stress [40]; for example, the trees in the karst zone often have thick and sponge leaves to reduce transpiration [41]; some plants can reduce the damage of a drought event by improving the activity of their antioxidant enzymes [42,43]. Such adaptive mechanisms can effectively reduce water loss and improve water use efficiency.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Ma et al analyzed the lightning activities in China from December 2010 to February 2020, and concluded that the southwestern and southeastern sides of the Yungui Plateau are lightning-prone areas in winter (Ma et al, 2022). In recent years, there has been a warming trend on the Yungui Plateau (Shi and Chen, 2018;Ma et al, 2019). However, to the best of our knowledge, the specific analysis of lightning activities of this region remains in 2015 (Wu et al, 2017).…”
Section: Introductionmentioning
confidence: 99%